2020
DOI: 10.26753/jikk.v16i2.419
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Berat Badan Lahir Rendah (Bblr)dengan Kejadian Stunting Pada Balita Usia 2-5 Tahun Di Desa Umbulrejo Kecamatan Ponjong Kabupaten Gunung Kidul

Abstract: Latar belakang: Stunting masih menjadi permasalahan kehidupan balita saat ini, stunting yang dialami oleh balita dapat berdampak buruk saat balita besar dan dewasa kelak. Dampak balita stunting dapat menurunkan kecerdasan sehingga dapat menurunkan kualitas sumber daya manusia di masa depan. BBLR diduga sebagai faktor resiko terjadinya stunting pada balita.Tujuan: Penelitian ini bertujuan untuk mengetahui hubungan BBLR dengan kejadian stunting pada balita usia 2-5 tahu di Desa Umbulrejo, Ponjong, Gunungkidul.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
1
0
0
6
Order By: Relevance
“…Recent research in Brebes district, found that there are relationship between low birth weight and stunting incidence with p value = 0.045 (11).Two studies in the same year are in line with this result, namely in the Bantul area states that there is a strong relationship between birth weight with the incidence of stunting in children aged 24-59 months in the region Girirejo Bantul Village (12). There are also a significant relationship between low birth weight and the incidence of stunting in toddlers aged 2-5 years in Umbulrejo Village, Gunungkidul with a value of p = 0.000 and OR 0.056 (13).…”
Section: The Relationship Between Low Birth Weight With the Incidence...supporting
confidence: 68%
“…Recent research in Brebes district, found that there are relationship between low birth weight and stunting incidence with p value = 0.045 (11).Two studies in the same year are in line with this result, namely in the Bantul area states that there is a strong relationship between birth weight with the incidence of stunting in children aged 24-59 months in the region Girirejo Bantul Village (12). There are also a significant relationship between low birth weight and the incidence of stunting in toddlers aged 2-5 years in Umbulrejo Village, Gunungkidul with a value of p = 0.000 and OR 0.056 (13).…”
Section: The Relationship Between Low Birth Weight With the Incidence...supporting
confidence: 68%
“…Hal ini akan menyebabkan anak berisiko terkena stunting. BBLR merupakan predictor penting dalam kesehatan dan kelangsugan hidup bayi yang baru lahir dan berhubungan dengan risiko tinggi pada anak 28 .…”
Section: Faktor Penyebab Stuntingunclassified
“…Hal tersebut dapat dilihat dari tampilan fisik berupa berat badan dan juga tinggi badan yang cenderung lebih kurus dan lebih pendek jika dibandingkan anak yang tidak BBLR (9). Bayi yang dilahirkan dengan berat badan kurang akan mengalami kesulitan dalam mengejar pertumbuhan terutama pada usia dua tahun pertama dan berakhir pada perawakan yang pendek atau stunting (10). Jika tidak dilakukan upaya penanganan yang tepat, stunting dapat memberikan dampak serius terhadap produktivitas di masa yang akan datang melalui hambatan kemampuan kognitif, kemampuan motorik, dan juga kecerdasan intelektual (11).…”
Section: Pendahuluanunclassified